SOLVENT EXTRACTION PROCESS FOR THE RECOVERY COBALT AND NICKEL FROM LOW-GRADE LATERITE USING BATCH RECYCLE SYSTEM - Sudibyo Sudibyo; Agus Junaedi; Muhammad Amin; Slamet Sumardi; Fajar Nurjaman; Bramantyo Bayu Aji; Yayat Iman Supriyatna; Lilis Hermida (Pusbindiklat - LIPI, 2018)
Low-grade laterite which contains nickel lower than 0.5 % is difficult to beprocessed using pyrometallurgy. One method which isable to solve this problem is solvent extraction. In thisstudy, a solvent extraction process using batch recycle methods has been successfully applied to separate nickel and cobalt from low-grade laterite. Sulphuric acid was used to leach laterite at atmospheric pressure. Meanwhile, cyanex in toluene was used as an organic solvent. Taguchi experimental design has been used to analyze and optimize the solvent extraction process using batch recycle methods. Taguchi analysis results show that the optimum conditions are at 7 of pH, 3 hours of time operation, 0.9 liter/minute of flow rate and 0.75 of organic/aqueous solutions ratio.